2020
DOI: 10.1097/tp.0000000000003151
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Association Between the Quantity of Human Peripheral Blood CXCR5+IFN-γ+CD8+ T Cells With De Novo DSA Production in the First Year After Kidney Transplant

Abstract: Background:We recently reported that a novel CXCR5 + IFN-γ + CD8 + T cell subset significantly inhibits posttransplant alloantibody production in a murine transplant model. These findings prompted the current study to investigate the association of human CD8 + T cells with the same phenotype with the development of de novo donor-specific antibody (DSA) after kidney transplantation. Methods:In the current studies, we prospectively and serially analyzed peripheral blood CD8 + and CD4 + T cell subsets and monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“… 32 A prospective study also concluded that the development of de novo donor‐specific antibodies (dnDSAs) was negatively correlated with the number of IFNγ + CXCR5 + CD8 + T cells in the peripheral blood, which was consistent with the antibody inhibition function of IFNγ + CXCR5 + CD8 + T cells. 33 In the current study, we observed that the percentage of CXCR5 + CD8 + T cells in the stable recipients group was higher than that in the CAD group. Based on the above results about the function of CXCR5 + CD8 + T cells, we speculated that CXCR5 + CD8 + T cells might be a subtype of CD8 T Ab supp population 31 or act like Treg cells with the function of reducing the number of Tfh cells and inhibiting the production of alloantibodies, 14 and performed as helpful cells for the maintenance of renal function in KTRs.…”
Section: Discussionsupporting
confidence: 44%
“… 32 A prospective study also concluded that the development of de novo donor‐specific antibodies (dnDSAs) was negatively correlated with the number of IFNγ + CXCR5 + CD8 + T cells in the peripheral blood, which was consistent with the antibody inhibition function of IFNγ + CXCR5 + CD8 + T cells. 33 In the current study, we observed that the percentage of CXCR5 + CD8 + T cells in the stable recipients group was higher than that in the CAD group. Based on the above results about the function of CXCR5 + CD8 + T cells, we speculated that CXCR5 + CD8 + T cells might be a subtype of CD8 T Ab supp population 31 or act like Treg cells with the function of reducing the number of Tfh cells and inhibiting the production of alloantibodies, 14 and performed as helpful cells for the maintenance of renal function in KTRs.…”
Section: Discussionsupporting
confidence: 44%
“…Transplant recipients who developed de novo DSA exhibited 2-fold lower quantity of CXCR5 1 CD8 1 T cells (and CXCR5 1 IFN-g 1 CD8 1 T cells) both pretransplant as well as posttransplant compared with recipients who did not develop DSA. Furthermore, pretransplant quantity of CXCR5 1 IFN-g 1 CD8 1 T cells <3,300 per million PBMCs was highly associated with the development of de novo DSA (area under the curve, 0.81; sensitivity, 93%; specificity, 62%) (53). This pretransplant immune assessment suggests that prospective kidney transplant recipients could be stratified into groups that are low or high risk for de novo DSA production.…”
Section: Clinical Correlations Of Human Cxcr5 1 Cd8 1 T Cellsmentioning
confidence: 85%
“…We have pursued studies in humans to determine whether or not CXCR5 + CD8 + T cells are detected in peripheral blood. Interestingly, we found in a prospective observational study that first‐time KTx recipients who develop de novo DSA have significantly reduced quantity of peripheral blood CXCR5 + CD8 + T cells (and activated CXCR5 + IFN‐γ + CD8 + T cells) compared to recipients that remain DSA‐free at one year posttransplant, despite transplantation under cover of the same induction and maintenance immunosuppressive regimen and achievement of equivalent target drug levels 63 . These findings raise the possibility that a homolog of murine antibody‐suppressor CXCR5 + CD8 + T cells exists in humans.…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, we found in a prospective observational study that first-time KTx recipients who develop de novo DSA have significantly reduced quantity of peripheral blood CXCR5 + CD8 + T cells (and activated CXCR5 + IFNγ + CD8 + T cells) compared to recipients that remain DSA-free at one year posttransplant, despite transplantation under cover of the same induction and maintenance immunosuppressive regimen and achievement of equivalent target drug levels. 63 These findings raise the possibility that a homolog of murine antibodysuppressor CXCR5 + CD8 + T cells exists in humans. Studies are ongoing to investigate the clinical utility of monitoring this cell subset as a biomarker to risk-stratify patients for the development of de novo DSA.…”
Section: Discussionmentioning
confidence: 99%